TRP Channels Role in Pain Associated With Neurodegenerative Diseases - Duitama, Milena; Vargas-López, Viviana; Casas, Zulma; Albarracin, Sonia L.; Sutachan, Jhon-Jairo; Torres, Yolima P. (Frontiers in Neuroscience, 2020)
Transient receptor potential (TRP) are cation channels expressed in both non-excitable and excitable cells from diverse tissues, including heart, lung, and brain. TRP channel family includes 28 isoforms that are activated by physical and chemical stimuli such as temperature, pH, osmotic pressure, and noxious stimuli. Recently, it has been shown that TRP channels are also directly or indirectly activated by reactive oxygen species. Oxidative stress plays an essential role in neurodegenerative disorders such as Alzheimer's and Parkinson's diseases, and TRP channels are involved in the progression of those diseases by mechanisms involving changes in the crosstalk between Ca2+ regulation, oxidative stress, and production of inflammatory mediators. TRP channels involved in nociception include members of the TRPV, TRPM, TRPA, and TRPC subfamilies that transduce physical and chemical noxious stimuli. It has also been reported that pain is a complex issue in patients with Alzheimer's and Parkinson's diseases, and adequate management of pain in those conditions is still in discussion. TRPV1 has a role in neuroinflammation, a critical mechanism involved in neurodegeneration. Therefore, some studies have considered TRPV1 as a target for both pain treatment and neurodegenerative disorders. Thus, this review aimed to describe the TRP-dependent mechanism that can mediate pain sensation in neurodegenerative diseases and the therapeutic approach available to palliate pain and neurodegenerative symptoms throughout the regulation of these channels.